Laparoscopic Lateral Suspension (LLS) for the Treatment of Apical Prolapse: A New Gold Standard? - Dällenbach, Patrick (Frontiers in Surgery, 2022)
Nowadays, the gold standard to treat apical pelvic organ prolapse (POP) is laparoscopic sacrocolpopexy (LSCP). However, LSCP is a difficult procedure associated with rare but potentially severe complications. Promontory dissection may expose to potential life-threatening intraoperative vascular injuries, and sacral roots or hypogastric nerve damage. There are also a few case reports of spondylodiscitis with consecutive lumbar vertebra bone erosion. Laparoscopic lateral suspension (LLS) with mesh is an alternative technique for apical POP repair. It lowers perioperative risks by avoiding sacral promontory preparation. Recent studies show similar anatomical and functional outcomes to LSCP, with the advantage of better preserving the vaginal axis. Moreover, LLS is well suited for hysteropexy which is important as an increasing number of women prefer uterine preservation during POP surgery. In this article, we discuss both techniques, and we share our opinion on a novel perspective in the treatment of apical POP with uterine preservation.